INNOVATIVE WATER-SAVING IRRIGATION TECHNOLOGY FOR AGRICULTURE IN ARID REGIONS OF SOUTH AFRICA - Usman Tariq; Rizky Franchitika; Kim Minho (Yayasan Adra Karima Hubbi, 2025)
Agriculture in the arid regions of South Africa faces major challenges related to water scarcity, which worsens the sustainability of the sector. Water-efficient irrigation technology has emerged as a potential solution to reduce water use and increase agricultural productivity. This study aims to evaluate the impact of water-saving irrigation technology on water use efficiency and crop yields in arid regions of South Africa. Quantitative and qualitative approaches were used in this study, involving 150 farmers as a sample, as well as questionnaire data analysis and in-depth interviews. The results of the study show that this technology is able to increase water use efficiency by up to 30%, increase crop yields by 20%, and reduce average operating costs by 15%. The conclusion of the study is that water-efficient irrigation technology plays an important role in improving the sustainability of agriculture in dry regions and can contribute to food security in South Africa. The adoption of this technology needs to be encouraged more widely through government support and training for farmers.